The TiO2 topotactic transformation assisted trapping of an atomically dispersed Pt catalyst for low temperature CO oxidation. Issue 29 (29th May 2019) - He, Yunping; Song, Xue-Zhi; Ding, Feng; Kang, Xiaolan; Sun, Feifei; Su, Qiaofeng; Tan, Zhenquan
Abstract : Atomically dispersed Pt catalysts are deposited on the rough surface of TiO2, which is synthesized via topotactic transformation from a NH4 TiOF3 mesocrystal. Abstract : Atomically dispersed Pt catalysts are synthesized on TiO2 with high activity and strong high temperature resistance by loading Pt in the process of converting the NH4 TiOF3 precursor to TiO2 by a topotactic transformation process. The atomically dispersed Pt catalyst displayed high catalytic activity for the low temperature CO oxidation reaction.